IMPLEMENTASI ACTIVE LEARNING DALAM PENINGKATAN MOTIVASI BELAJAR SISWA DI SMP NEGERI 1 JANGKAR - Abd. Aziz Noer (LP2M Universitas Ibrahimy, 2017)
Learning process requires a professional teacher is carry out its duties, because to achieve success in the learning process is expect to master learning strategy, learning model and able to manage the class because students are different both in terms of catchment psychology of learning._x000D_ Active learning is a learning model that seeks to make active, creative, effective and enjoyable learning between teachers and students. In using active method of learning is needed expertise, both in terms expertise use of creative methods and classroom management. Because sometimes the reality in field is different from what has been prepared in active application of learning teachers must use multiple methods in accordance with taught material, and conducive management so that students are happy and not bored in receiving lessons._x000D_ Supporting factors and obstacles in improving learning motivation students are the supporting factors of PAI teacher competence, support from school principals both in terms of motivation and available facility as well as support from other teachers, and inhibiting factors lack of parental support for education. The solution to overcome obstacles is to establish good communication with guardian students such as meeting at a certain time for maximizing the school committee and always encourage students with strategies such as active learning that can make the spirit and motivated in learning.